Die hermeneutiek van kerkgeskiedenis en "teologiegeskiedenis": "n "Nuwe paradigma" vir kerkgeskiedenis - Labuschagne, JP (HTS teologiese studies, 2008)
The hermeneutics of church history and the “history of theology”: A “new paradigm” for church history This study reflects on a new paradigm for church history. The traditional definition of church history, as a study of the growth and development of the church in all its facets, constricts church history to disclose too little about too much. This paper argues in favor of all that can be gained by a new paradigm for church history as a history of theology. A history of theology focuses more on the different theologies and the theological debates of the different periods in the history of the church.